The Relevance of the Idea of “Community of Inquiry” to Contemporary Ethics. In memory of Matthew Lipman (†2010) - Tibaldeo, Roberto Franzini (ETHICS IN PROGRESS, 2011)
Problematic and complex aspects of democratic life ? such as the teaching of the concept of civil liberties, the spreading of responsible participation and pluralistic dialogue, the mutual understanding of different cultures and individuals, and the fulfilment of a common civil life based upon shared rules, procedures, and reasonable dialogue ? are not yet solved and certainly need to be frequently revisited and reviewed